2021
DOI: 10.3390/vaccines9080833
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of a Spike Glycoprotein Domain A-Specific Neutralizing Single-Chain Variable Fragment against Porcine Epidemic Diarrhea Virus

Abstract: The emergence of the genotype (G) 2 and re-emergence of the G1 porcine epidemic diarrhea virus (PEDV) has caused severe economic impacts in the past decade. Developments of efficient vaccines against new variants of PEDV have been challenging, not least because of the difficulties in eliciting mucosal and lactogenic immunity. A single-chain fragment variable (scFv) capable of efficient antigen recognition is an alternative to vaccination and treatment of a viral infection. In the present study, the variable re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Taken all the data together, the enhancing epitope of the PEDV S1 subunit that may cause ADE was found to be located at the C terminus of the S1-0 sub-domain and S1-BCD. Although the exact residues that participate in the epitope formation need further elucidation (such as by co-crystallography), the finding in this study together with the information on the known S1 neutralizing epitopes identified previously (Chang et al, 2002(Chang et al, , 2019(Chang et al, , 2021Cruz et al, 2008;Sun et al, 2008;Okda et al, 2017;Ho et al, 2020;Tien et al, 2021;Thavorasak et al, 2022) should be useful in designing a safe PEDV vaccine, i.e., by using a recombinant spike (S) protein whose C-terminal portion of S1-0 and S1-BCD have been deleted and contain only the neutralizing B-cell epitopes along with appropriate T-cell epitopes as immunogens in a subunit protein vaccine or by using the respective DNA counterparts as a DNA vaccine.…”
Section: A B Csupporting
confidence: 50%
“…Taken all the data together, the enhancing epitope of the PEDV S1 subunit that may cause ADE was found to be located at the C terminus of the S1-0 sub-domain and S1-BCD. Although the exact residues that participate in the epitope formation need further elucidation (such as by co-crystallography), the finding in this study together with the information on the known S1 neutralizing epitopes identified previously (Chang et al, 2002(Chang et al, , 2019(Chang et al, , 2021Cruz et al, 2008;Sun et al, 2008;Okda et al, 2017;Ho et al, 2020;Tien et al, 2021;Thavorasak et al, 2022) should be useful in designing a safe PEDV vaccine, i.e., by using a recombinant spike (S) protein whose C-terminal portion of S1-0 and S1-BCD have been deleted and contain only the neutralizing B-cell epitopes along with appropriate T-cell epitopes as immunogens in a subunit protein vaccine or by using the respective DNA counterparts as a DNA vaccine.…”
Section: A B Csupporting
confidence: 50%
“…One previous study reported a neutralizing epitope located on residues 435-485 of the PEDV S1A subdomain. However, mAbs directed against that epitope was shown to neutralize the infectivity of only G2b, and not the G1 PEDV classical strain CV777 [29,57]. This might have been due to the critical amino acid substitutions that occurred in the residues 435-485 region of the G2b variant that were different from those of the CV777 classical G1 strain.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, for safety reasons, next generation vaccines should elicit broadly neutralizing antibodies and not enhancing antibodies (i.e., the vaccine should contain only virus neutralizing epitopes). For PEDV vaccines, multiple neutralizing epitopes of the PEDV S1 with vaccine potential have been identified [18,20,27,29,[56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…PEDV is an enveloped, positive-sense, single-stranded RNA virus, belonging to the genus Alphacoronavirus in the family Coronaviridae of the order Nidovirales. Among the four PEDV structural proteins, namely spike (S), envelope (E), membrane (M), and nucleocapsid (N), the S protein dominates the surface of virus particles and mediates direct binding to cell receptors, is a major target to induce neutralizing antibodies [ 9 , 10 , 11 ], and can also be the target in vaccine development [ 12 ]. In coronavirus, as the major surface protein that directly interacts with cellular receptors, the S protein bears the greatest evolutionary pressure and the S gene contains the most variable regions in the entire PEDV genome, including the strains reported in the United States in 2013–2014 [ 8 , 13 ] with insertions and deletions in the S gene (S-INDEL).…”
Section: Introductionmentioning
confidence: 99%